LAYANAN BIMBINGAN KELOMPOK SECARA DARING DENGAN TEKNIK DISKUSI UNTUK MENINGKATKAN KONTROL DIRI SISWA PENGGUNA SOSIAL MEDIA DI SMP - Risma Pahlawati; Heris Hendriana; Maya Masyita Suherman (IKIP Siliwangi, 2021)
Online group guidance services are a process of assistance carried out by BK teachers or counselors to students or counselees using online media. The purpose of this study was to determine the implementation, student and teacher responses, the difficulties encountered and the obstacles that occurred in the implementation of group guidance services conducted online. The research method used in this study is to use a qualitative approach with a descriptive type of approach. Data collection techniques used are observation, interviews and documentation. The subjects in this study consisted of a primary subject, namely one BK teacher and 4 students, and a secondary subject consisting of the principal and one homeroom teacher. The results of the study indicate that online group guidance services using discussion techniques can help students improve their self-control and students can be wiser in language on social media and can better manage the time when to do assignments and when is the right time to play social media.Keywords: Self-Control of Social Media Users, Group Guidance, Discussion Techniques